Geoinformational support for modeling the efficiency of crop cultivation in crop rotations - Shulgan, Roman; Yanchuk, Oleksandr; Nikolaichuk, Kateryna; Kibysh , Anastasiia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
In the article was developed a tool in the ModelBuilder application, which evaluate the economic efficiency of the use of the selected plot of land and provide an opportunity to determine the most effective scientifically based crop rotation using the modeling method. The indicator of effective use is the profitability of growing products, when applying different sets of agricultural crops scientifically based crop rotation. The model was tested on a specific field of an agricultural enterprise with different crop rotation options, as well as when applying the same crop scheme for different fields. У статті розроблено інструмент у середовищі ModelBuilder, призначений для оцінювання економічної ефективності використання вибраної земельної ділянки та визначення найбільш результативної науково обґрунтованої сівозміни за допомогою моделювання. Критерієм ефективного використання виступає показник рентабельності вирощування сільськогосподарської продукції за різних варіантів наборів культур у науково обґрунтованій сівозміні. Запропоновану модель апробовано на конкретному полі сільськогосподарського підприємства з використанням різних варіантів сівозмін, а також за умови застосування ідентичної схеми культур для різних полів.